Fostering Creative Thinking in the Digital Era: Integrating Ethnoscience and TikTok into Science Edutainment - Maissy Widiastuti; Hendra Febriyanto (Jurnal Pendidikan MIPA, 2026)
Students' creative thinking skills remain relatively low in science learning, mainly due to a limited variety of learning media and a lack of integration of local wisdom. This study aims to develop Ethno-Tok edutainment-based learning media that integrates the ethnoscience of making nopia cakes into TikTok video content to train the creative thinking skills of seventh-grade students at SMP Negeri 1 Kejobong. The novelty of this study lies in integrating ethnoscience, the TikTok social media platform, and the edutainment approach into a structured, contextually grounded design for science learning media. This study used the Research and Development (R&D) method with the ADDIE model, comprising the Analysis, Design, Development, Implementation, and Evaluation stages. There were 42 students in the study, including 10 in the small group and 32 in the large group. Data were collected through expert validation, student response questionnaires, and creative thinking skills essay tests assessing the indicators of fluency, flexibility, originality, and elaboration. Data analysis was performed descriptively and inferentially using the Shapiro-Wilk normality test and the paired sample t-test. The validation results showed that the Ethno-Tok media was in the highly feasible category, and student responses were in the very good category. Students' creative thinking skill scores increased significantly from the pretest to the posttest, both in the small group (23.6 to 85.8) and the large group (24.06 to 88.19). The paired-samples t-test showed a significant difference between pretest and posttest scores (p < 0.05). The N-gain analysis showed that the fluency and flexibility indicators were in the very good category, while originality and elaboration were in the good category. Ethno-Tok edutainment media shows potential to support the improvement of students' creative thinking skills in science learning through a local culture-based approach and project-based learning. The integration of local wisdom contexts with digital media familiar to students can strengthen learning engagement and conceptual understanding. However, because this study did not include a control group, the findings should be interpreted cautiously and considered preliminary evidence that requires further testing through experimental research designs. Keywords: ethnoscience, TikTok, edutainment, creative thinking skills.